KEBIJAKAN PENGGUNAAN SANKSI PIDANA DALAM PERUNDANG–UNDANGAN HUKUM ADMINISTRASI UNDANGAN HUKUM ADMINISTRASIUNDANGAN HUKUM ADMINISTRASI UNDANGAN HUKUM ADMINISTRASI - Sulaiman, Eman (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractThe use of criminal sanctions as the main sanction has indicated the extent towhich the level of understanding of the legislators to the problem of